Reconciling the Issues And Concerns of the Place of Rhetoric in Communication for Development Practice: an Essay - Samuel Ayodele Ojurungbe (International Journal of Integrated Science and Technology, 2024)
This paper was inspired by the clear signals the researcher received in his first few weeks as a graduate student of Development Communication at the University of Philippines Los Banos (UPLB), which pointed in the direction that Rhetoric had no place or significant role to play in Communication for. Development/Development Communication practice. It aims at theorizing that Rhetoric has a place, and is relevant to Development Communication. It attempts this through an exploration of existing literature for foundations of a number of assumptions that appeared to have informed decisions on the usability of Rhetoric in Communication for Development. paper concludes that beyond answers to the discursive positions of the essay,a thorough understanding of the foundational elements of Rhetoric may help strengthen the quality of development practitioners by preparing and equipping them with the right measure of sensitivity, and an appreciation that the field of development is primarily made of ‘people’ and ‘communities’, and most especially in finding truthful answers to whether Rhetoric in its classical and contemporary incarnations, can offer an alternative way of addressing some of today’s issues of development/social change and/or ensure a better grasp of principles and concepts of social change.